Local Community’s Knowledge and Perception towards Freshwater Turtle Conservation in Southern Sumatra, Indonesia - Tiara, Alma; Kusrini, Mirza Dikari; Sunkar, Arzyana; Guntoro, Joko (Jurnal Manajemen Hutan Tropika, 2025)
The conservation of freshwater turtles relies on local knowledge and perceptions. This phenomenon is especially significant for communities located near turtle habitats. This study aims to investigate the influence of local communities' knowledge and perceptions of freshwater turtles on their attitudes, behaviors, and the resulting conservation outcomes for these species. Knowledge encompasses the empirical understanding of turtle species, their ecological roles, and conservation statuses. Perceptions encompass the subjective beliefs, attitudes, and values influenced by culture that communities hold regarding these species. The research was carried out in three river systems of southern Sumatra, involving interviews with 133 participants through a semi-structured approach that included closed and semi-open questionnaires, alongside a recollection method utilizing photographs as a tool. Identification was successful for only 8 of the 12 depicted turtle species, and merely one-third of the freshwater turtle eggs were identifiable. The most widely recognized species include the ambiona box turtle (Cuora amboinensis), Malaysian giant turtle (Orlitia borneensis), soft-shelled turtle (Amyda cartilaginea), and black marsh turtle (Siebenrockiella crassicollis). While most perceptions indicated a favorable attitude towards freshwater turtle conservation, negative behaviors persist that may adversely affect turtle populations.